Changes of the corticospinal tract in the unaffected hemisphere in stroke patients: A diffusion tensor imaging study. (2nd January 2016) - Jang, Sung Ho; Yi, Ji Hyun; Choi, Byung Yeon; Chang, Chul Hoon; Jung, Young Jin; Lee, Han Do; Yeo, Sang Seok
Abstract: We investigated changes of the corticospinal tract (CST) in the unaffected hemisphere according to severity of the CST injury, using diffusion tensor imaging (DTI). According to the severity of the CST injury in the affected hemisphere, the stroke patients showed different aspects of fiber volume increment of the CST in the unaffected hemisphere; the fiber volume was increased in the early phase in patients with mild injury of CST and later phase in patients with severe injury of CST.